Analisis Ekstensifikasi Pajak Atas Kebijakan NIK Menjadi NPWP dalam Rangka Meningkatkan Kepatuhan Wajib Pajak di Kantor Pelayanan Pajak Pratama Bekasi Barat Tahun 2022 - Fachrul Rozy Ramadhan Bachmid; Jiwa Pribadi Agustianto (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Tax extensification through the Policy of Integrating the Population Identification Number into the Taxpayer Identification Number is a new breakthrough of the Directorate General of Taxes which comes from the many public complaints about the number of government identity numbers that need to be owned, therefore the Single Identification Number (SIN) will be implemented between the Population Identification Number and the Taxpayer Identification Number. This research was conducted to find out how the Tax Extensification of the Population Identification Number Policy becomes a Taxpayer Identification Number in order to increase compliance of individual taxpayers at the West Bekasi Pratama Tax Service Office in 2022. This research method uses a qualitative descriptive method. The results of this study indicate that the implementation of Extensification on the existence of the Population Identification Number policy into a Taxpayer Identification Number has been able to increase the number and compliance of taxpayers. However, there are still obstacles in the form of many taxpayers who feel complicated by the matching process due to differences in data in the Population Identification Number and in the Taxpayer Identification Number which affects the initial process in the form of matching has not been fully achieved, and there is still a lack of tax education owned by taxpayers. And some of the ways that can be done to help Extensification of this policy is to conduct intensive and equitable socialization and counseling by utilizing technology and social media so that the education and information conveyed can be received by taxpayers.